Mortality risk following end-of-life caregiving: A population-based analysis of hospice users and their families - Hollingshaus, Mike; Smith, Ken R.; Meeks, Huong; Ornstein, Katherine; Iacob, Eli; Tay, Djin; Stephens, Caroline; Utz, Rebecca L. (Social science & medicine (1982), 2024)
Experiencing the death of a family member and providing end-of-life caregiving can be stressful on families – this is well-documented in both the caregiving and bereavement literatures. Adopting a linked-lived theoretical perspective, exposure to the death and dying of one family member could be conceptualized as a significant life stressor that produces short and long-term health consequences for surviving family members. This study uses familial-linked administrative records from the Utah Population Database to assess how variations in family hospice experiences affect mortality risk for surviving spouses and children. A cohort of hospice decedents living in Utah between 1998 and 2016 linked to their spouses and adult children (n = 37,271 pairs) provides an ideal study population because 1) hospice typically involves family members in the planning and delivery of end-of-life care, and 2) hospice admission represents a conscious awareness and acknowledgment that the decedent is entering an end-of-life experience. Thus, hospice duration (measured as the time between admission and death) is a precise measure of the family's exposure to an end-of-life stressor. Linking medical records, vital statistics, and other administrative microdata to describe decedent-kin pairs, event-history models assessed how hospice duration and characteristics of the family, including familial network size and coresidence with the decedent, were associated with long-term mortality risk of surviving daughters, sons, wives (widows), and husbands (widowers). Longer hospice duration increased mortality risk for daughters and husbands, but not sons or wives. Having other family members in the state was protective, and living in the same household as the decedent prior to death was a risk factor for sons. We conclude that relationship type and sex likely modify the how of end-of-life stressors (i.e., potential caregiving demands and bereavement experiences) affect health because of normative gender roles. Furthermore, exposure to dementia deaths may be particularly stressful, especially for women. •Exposure to end-of-life caregiving may increase mortality risk for surviving family.•Longer hospice duration and being the only nearby family member are risk factors.•Gender and relationship type (child or spouse) modify survivors' mortality risk.•Having more family members is protective against survivors' mortality risk.•Having a spouse with dementia is particularly risky for surviving widows' health.